High performance composite Pr4Ni3O10±δ-Ce0.75Gd0.1Pr0.15O2−δ solid oxide cell air electrode - Xie,Z; Jang,I; Ouyang,M; Hankin,A; Skinner,S (JPhys Energy, 2023)
A composite electrode composed of Pr4Ni3O10±δ - Ce0.75Gd0.1Pr0.15O2−δ (50 wt. % - 50 wt. %) was thoroughly investigated in terms of the electrochemical performance as a function of microstructure. The electrochemical performance was characterized by electrochemical impedance spectroscopy and the microstructures, characterized by focused ion beam-scanning electron microscopy and 3D reconstructions, were modified by changing the particle size of Pr4Ni3O10±δ and the electrode thickness. The distribution of relaxation time (DRT) method was applied to help resolve electrochemical processes occurring in the electrodes. It was found that an appropriate increase in electrode thickness and an appropriate decrease in particle size enhanced the oxygen reduction reaction kinetics. The
lowest area specific resistance obtained in this study at 670 °C under pO2 of 0.21 atm was 0.055 Ω cm2. Finally, a comparison to the Adler Lane Steele (ALS) model was made and the main active site for the oxygen reduction reaction was concluded to be triple phase boundaries. A fuel cell made of the composite material as the cathode was fabricated and tested. The peak power density was 1
Wcm−2 at 800 °C, which demonstrates this composite material is promising for SOFC cathodes.